Participation of people living with disabilities in physical activity: a global perspective. Issue 10298 (31st July 2021) - Martin Ginis, Kathleen A; van der Ploeg, Hidde P; Foster, Charlie; Lai, Byron; McBride, Christopher B; Ng, Kwok; Pratt, Michael; Shirazipour, Celina H; Smith, Brett; Vásquez, Priscilla M; Heath, Gregory W
Summary: Approximately 1·5 billion people worldwide live with a physical, mental, sensory, or intellectual disability, about 80% of which are in low-income and middle-income countries. This Series paper provides a global overview of the prevalence, benefits, and promotion policies for physical activity for people living with disabilities (PLWD). PLWD are 16–62% less likely to meet physical activity guidelines and are at higher risk of serious health problems related to inactivity than people without disabilities. Meta-analyses have shown that physical activity has beneficial effects on cardiovascular fitness (average standardised mean difference [SMD] 0·69 [95% CI 0·31–1·01]), musculoskeletal fitness (0·59 [0·31–0·87]), cardiometabolic risk factors (0·39 [0·04–0·75]), and brain and mental health outcomes (0·47 [0·21–0·73]). These meta-analyses also show that health benefits can be achieved even with less than 150 min of physical activity per week, and suggest that some physical activity is better than none. Meta-analyses of interventions to increase physical activity for PLWD have reported effect sizes ranging from SMD 0·29 (95% CI 0·17–0·41, k=10) to 1·00 (0·46–1·53, k=10). There is increasing awareness among policy makers of the needs of PLWD for full participation in physical activity. Physical activity action plans worldwide must be adequately resourced, monitored, and enforced to truly advance the fundamental rights of PLWD to fully participate in physical activity.